Leishmania tropica: The effect of darkness and light on biological activities in vitro - Allahverdiyev, Adil M.; Koc, Rabia Cakir; Ates, Sezen Canim; Bagirova, Malahat; Elcicek, Serhat; Oztel, Olga Nehir (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2011)
Leishmania parasites can be exposed to effects of light in their vectors and hosts, at various periods. However, there is no information about the effects of light on Leishmania parasites. The aim of this study is to investigate the effects of light on various cell parameters of Leishmania tropica, in vitro. All experiments were conducted on L. tropica promastigotes and amastigote-macrophage cultures, using flow cytometric analysis, MU and phenol-sulfuric acid assay. DAPI and Giemsa. The results showed that the morphology of parasites has changed; the cell cycle has been affected and this caused parasites to remain at G0/G1 phase. Furthermore the proliferation, infectivity, glucose consumption and mitochondrial dehydrogenase activities of parasites were decreased. Thus, for the first time, in this study, the effects of light on biological activities of Leishmania parasites were shown. These new information about parasites' biology, would be very important to investigate the effects of light on the parasites in infected vectors and hosts. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Leishmania; Parasitology; Light; CELL-CYCLE REGULATION; COLORIMETRIC ASSAY; VISIBLE-LIGHT